Multilayer film, packaging material and package
A multi-layer polypropylene film with propylene polymers and zinc oxide particles addresses odor issues in retort packaging by adsorbing sulfur compounds, maintaining transparency, and ensuring heat resistance and flexibility.
Patent Information
- Application Number
- JP2024190291
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2041-01-05
AI Technical Summary
Existing packaging materials, particularly those used for retort foods, suffer from odor deterioration due to sulfur compounds during high-temperature processing, leading to reduced visibility of the contents.
A multi-layer polypropylene film is developed with specific compositions of propylene polymers and zinc oxide particles, balancing odor adsorption and transparency by incorporating propylene solo polymer, propylene ethylene copolymers, and zinc oxide particles in strategic layers.
The film effectively adsorbs sulfur odors while maintaining high transparency, ensuring better content visibility and retaining heat resistance and flexibility, making it suitable for retort packaging applications.
Smart Images

Figure 2025013378000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a multilayer film, a packaging material, and a package. More specifically, the present invention relates to a polypropylene-based multilayer film that can be suitably used as a sealant film for packaging bags even in severe treatments such as boiling water treatment and retort treatment, and a packaging material and a package obtained by using the polypropylene-based multilayer film. [Background technology]
[0002] Polypropylene-based films have excellent rigidity and heat resistance, and are inexpensive, so they are sometimes used as sealant films in various packaging materials such as food packaging. One of their main uses is as packaging materials for retort foods, which are pasteurized and sterilized by high-temperature pressure treatment.
[0003] In packaged foods such as retort foods that are sterilized or pasteurized at high temperatures, the contents can deteriorate or denature due to heat sterilization during manufacturing or long-term storage, resulting in the emission of a denatured odor. The sources of this denatured odor are carbohydrates, fats and oils, proteins, etc., and among these, the denatured odor of proteins contained in meat, fish, soybeans, eggs, etc., and especially the sulfur odor derived from sulfur compounds, are often problematic.
[0004] Patent Document 1 proposes a packaging body characterized in that a coating agent consisting of a zinc compound and a solvent or dispersion medium is applied to the surface of an oxygen barrier material, which is a film consisting of a resin layer containing a polycarboxylic acid polymer formed on a base film. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2013-018551 A Summary of the Invention [Problem to be solved by the invention]
[0006] Although the packaging material described in Patent Document 1 exhibits an odor adsorption function against sulfur odors, there is room for improvement in terms of visibility of the contents.
[0007] The present invention has been made in view of the above circumstances, and has an object to provide a multilayer film that is excellent in odor adsorption properties for sulfur odors generated from contents and in visibility of contents. Another object of the present invention is to provide a packaging material and a package obtained by using the multilayer film. [Means for solving the problem]
[0008] As a result of intensive research to solve the above problems, the inventors discovered that it is important to incorporate a predetermined amount of a mixture of different propylene-based polymers into the outer layer of a polypropylene-based multilayer film and to incorporate zinc oxide particles into at least one of the multiple layers, and thus completed the present invention.
[0009] A multilayer film according to one aspect of the present invention comprises a first outer layer which is a heat seal layer containing a propylene homopolymer (A) and a propylene-ethylene random copolymer (B), an inner layer which contains a propylene-ethylene block copolymer (C) and an ethylene-propylene copolymer elastomer (D), and a second outer layer which contains the propylene homopolymer (A) and the propylene-ethylene random copolymer (B) in this order, wherein at least one of the inner layer and the second outer layer further contains zinc oxide particles, and the content of the zinc oxide particles is 0.030 to 0.25 g / m per unit area of the multilayer film. 2 It is.
[0010] In the above multilayer film, the amount of zinc oxide particles to be added can be reduced by blending zinc oxide particles in the polypropylene film. This makes it possible to suppress a decrease in the transparency of the film while ensuring odor adsorption for the sulfur odor generated from the contents. Such a film can further improve the visibility of the contents compared to a case where a coating agent containing zinc oxide particles is used (for example, the above Patent Document 1). This effect is particularly suitable for food retort treatment applications in which a sulfur odor is generated during retort treatment.
[0011] In one embodiment, the average spherical equivalent diameter of zinc oxide particles may be 100 nm or less. This increases the surface area of zinc oxide, making it easier to obtain odor adsorption properties against sulfur odor. In addition, since the average spherical equivalent diameter of zinc oxide is 100 nm or less and is smaller than the wavelength of visible light, light dispersion can be suppressed, making it easier to obtain better transparency.
[0012] In one embodiment, the first outer layer and the second outer layer contain 70 to 30 parts by mass of a propylene homopolymer (A) and 30 to 70 parts by mass of a propylene-ethylene random copolymer (B) having an ethylene content of 5% by mass or less, and the second outer layer may further contain zinc oxide particles. This makes it easier to suppress surface irregularities that reduce the transparency of the film. This makes it possible to achieve both better heat resistance and transparency.
[0013] In one embodiment, the inner layer contains 90 to 50 parts by mass of the propylene-ethylene block copolymer (C) and 10 to 50 parts by mass of the ethylene-propylene copolymer elastomer (D), and may further contain zinc oxide particles, which maintains the flexibility of the film and makes it easier to obtain excellent cold impact resistance.
[0014] In one embodiment, the total thickness of the first outer layer and the second outer layer may be 25 to 42% of the thickness of the multilayer film, which makes it easier to achieve both transparency and heat sealability.
[0015] In one embodiment, the thickness of the inner layer may be 30 μm or more, which makes it easier to maintain the flexibility of the film and to obtain excellent cold impact resistance.
[0016] A packaging material according to one aspect of the present invention includes the multilayer film described above and a substrate.
[0017] A package according to one aspect of the present invention is produced from the above-described packaging material. Effect of the Invention
[0018] According to the present invention, it is possible to provide a multilayer film having excellent odor adsorption properties against a sulfur odor generated from a content and excellent visibility of the content. The present invention also provides a packaging material and a package obtained by using the multilayer film. [Brief description of the drawings]
[0019] [Figure 1] FIG. 1 is a cross-sectional view of a multilayer film according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view of a packaging material according to one embodiment of the present invention. [Diagram 3] FIG. 3 is a diagram showing the total heat of fusion of the propylene-ethylene random copolymer (B) used in the examples and the results of dividing the heat of fusion at 135° C. [Figure 4] FIG. 4 is a distribution diagram of the equivalent sphere diameters of zinc oxide particles in the film produced in Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] <Multilayer film> Fig. 1 is a cross-sectional view of a multilayer film according to one embodiment of the present invention. The multilayer film 10 includes a first outer layer 1a, an inner layer 2, and a second outer layer 1b in this order. The multilayer film can be used as a polypropylene-based non-stretch sealant film.
[0021] [First outer layer and second outer layer] The first outer layer and the second outer layer contain a propylene homopolymer (A) and a propylene-ethylene random copolymer (B). The first outer layer and the second outer layer may be formed from a propylene homopolymer (A) and a propylene-ethylene random copolymer (B). The first outer layer and the second outer layer may be collectively referred to simply as outer layers. The first outer layer and the second outer layer may have the same composition or different compositions. When used as a packaging material, the first outer layer serves as a heat seal layer and is arranged to contact the contents.
[0022] (Propylene homopolymer (A)) The propylene homopolymer (A) is not particularly limited in its production method, but can be obtained by, for example, a method of homopolymerizing propylene using a Ziegler-Natta type catalyst, a metallocene catalyst, or a half metallocene catalyst. By including the propylene homopolymer (A) in the outer layer, excellent heat resistance can be imparted to the outer layer.
[0023] The propylene homopolymer (A) may have a melting onset temperature of 150° C. or higher and a melting peak temperature of 155° C. or higher as measured by differential scanning calorimetry (JIS K 7121). A polymer having both a melting onset temperature and a melting peak temperature within this range has excellent heat resistance, and is unlikely to fuse on the inner surface of a packaging bag after, for example, a retort treatment at a high temperature.
[0024] As the propylene homopolymer (A), those having a melt flow rate (MFR: ISO 1133) (temperature 230°C, load 2.16 kg) in the range of 2.0 to 7.0 g / 10 min can be used. The melt flow rate is a parameter indicating the fluidity of a polymeric material when melted, and is also a parameter indicating the molecular weight. Therefore, if the melt flow rate is too high, the impact resistance of the polymeric material is likely to decrease, and if it is too low, the load on the extruder during molding processing increases, the processing speed decreases, and the productivity is likely to decrease. From these viewpoints, the melt flow rate can be 2.0 to 7.0 g / 10 min, and may be 2.0 to 5.0 g / 10 min.
[0025] (Propylene-ethylene random copolymer (B)) The method for producing the propylene-ethylene random copolymer (B) is not particularly limited, but it can be obtained, for example, by copolymerizing ethylene as a comonomer into the main monomer consisting of propylene using a Ziegler-Natta type catalyst, a metallocene catalyst, or a half metallocene catalyst. By containing the propylene-ethylene random copolymer (B) in the outer layer, a multilayer film with excellent transparency can be obtained.
[0026] The propylene-ethylene random copolymer (B) may have a melting onset temperature of 140°C or higher and a melting peak temperature of 145°C or higher when measured by differential scanning calorimetry (JIS K 7121). A copolymer having both a melting onset temperature and a melting peak temperature within this range has excellent heat resistance, and is unlikely to fuse on the inner surface of a packaging bag after, for example, a severe retort treatment at 135°C for 40 minutes.
[0027] For the propylene-ethylene random copolymer (B), the heat of fusion ΔH on the higher side than the measurement temperature of 135°C when differential scanning calorimetry (JIS K 7121) was performed. h and the heat of fusion on the low temperature side ΔH l Ratio to ΔH h / ΔH l A ratio in the range of 1.5 to 2.5 can be used. By keeping the ratio at or below the upper limit, the flexibility of the film is maintained, edge tearing of the heat-sealed portion after retort treatment can be suppressed, and the heat-seal strength is less likely to decrease. The lower limit of the ratio can be set to 1.5, from the viewpoint that fusion is less likely to occur on the inner surface of the packaging bag after retort treatment.
[0028] The ethylene content of the propylene-ethylene random copolymer (B) can be 5% by mass or less. By having the ethylene content be equal to or less than the upper limit, the heat resistance is not excessively decreased while maintaining the transparency, and it becomes easier to suppress fusion on the inner surface of the packaging bag after retort treatment. From this viewpoint, the ethylene content may be 4.5% by mass or less, or may be 4% by mass or less. The lower limit of the ethylene content is not particularly limited, but from the viewpoints of maintaining the flexibility of the film, suppressing edge tearing at the heat-sealed portion after retort treatment, and making it difficult for the heat-seal strength to decrease, it can be 2% by mass.
[0029] The ethylene content of the propylene-ethylene random copolymer (B) can be measured according to the quantitative method for ethylene content (IR method) described on pages 412-413 of the Polymer Analysis Handbook (May 10, 2013, 3rd printing) edited by the Polymer Analysis Roundtable of the Japan Analytical Society.
[0030] The outer layer may contain 70 to 30 parts by mass of a propylene homopolymer (A) and 30 to 70 parts by mass of a propylene-ethylene random copolymer (B) having an ethylene content of 5% by mass or less. When the content of the propylene homopolymer (A) is 30 parts by mass or more, excellent heat resistance is easily maintained. Furthermore, when the content of the propylene homopolymer (A) is 70 parts by mass or less, that is, when the content of the propylene-ethylene random copolymer (B) having an ethylene content of 5% by mass or less is at least 30 parts by mass or more, excellent transparency and heat sealability are easily exhibited. From these viewpoints, the outer layer may contain 60 to 40 parts by mass of a propylene homopolymer (A) and 40 to 60 parts by mass of a propylene-ethylene random copolymer (B).
[0031] [Inner layer] The inner layer contains a propylene-ethylene block copolymer (C) and an ethylene-propylene copolymer elastomer (D). The inner layer may be formed from the propylene-ethylene block copolymer (C) and the ethylene-propylene copolymer elastomer (D).
[0032] (Propylene-ethylene block copolymer (C)) Propylene-ethylene block copolymer (C) is a copolymer that can be obtained by producing a propylene polymer (C1) in the first step, and then producing an ethylene-propylene copolymer (C2) by gas phase polymerization in the second step. Propylene-ethylene block copolymer (C) is not a block copolymer in which a propylene polymer end and an ethylene-propylene copolymer end are bonded, but a type of blend copolymer. By containing propylene-ethylene block copolymer (C) in the inner layer, the flexibility of the film is maintained, edge cutting of the heat-sealed part after retort treatment can be suppressed, and excellent heat sealability can be easily obtained.
[0033] The propylene-ethylene block copolymer (C) may have a melt flow rate (MFR: ISO 1133) (temperature 230°C, load 2.16 kg) in the range of 0.5 to 2.5 g / 10 min. If the melt flow rate is too high, the impact resistance of the film is likely to decrease, and if it is too low, the load on the extruder during molding increases, the processing speed decreases, and the productivity is likely to decrease. From these viewpoints, the melt flow rate may be 0.5 to 2.5 g / 10 min., or may be 1.0 to 2.0 g / 10 min.
[0034] The propylene-ethylene block copolymer (C) may contain 90 to 60% by mass of the propylene polymer (C1) and 10 to 40% by mass of the ethylene-propylene copolymer (C2). When the amounts of each component are within these ranges, excellent heat sealability is easily obtained.
[0035] The ethylene content of the ethylene-propylene copolymer (C2) contained in the propylene-ethylene block copolymer (C) is not particularly limited, but can be in the range of 20 to 40 mass%. By having the ethylene content be equal to or less than the upper limit, the tackiness of the product can be suppressed, and contamination due to the tackiness of the product during production is unlikely to occur, making it easier to maintain excellent productivity. By having the ethylene content be equal to or more than the lower limit, the flexibility of the film can be maintained, and edge tearing of the heat-sealed portion after retort treatment can be suppressed, making it easier to obtain excellent heat-sealability.
[0036] (Ethylene-propylene copolymer elastomer (D)) The ethylene-propylene copolymer elastomer (D) can be obtained by, for example, a slurry polymerization method carried out in the presence of an inert hydrocarbon such as hexane, heptane, kerosene, or a liquefied α-olefin solvent such as propylene, or a gas phase polymerization method without a solvent. Specifically, the ethylene-propylene copolymer elastomer (D) can be obtained by a known multi-stage polymerization method. That is, it is a polymerized type high rubber content polypropylene-based resin obtained by polymerizing propylene and / or propylene-α-olefin polymer in the first reaction stage and then copolymerizing propylene and α-olefin in the second reaction stage. By containing the ethylene-propylene copolymer elastomer (D) in the inner layer, it is easy to impart flexibility to the film, edge cutting of the heat-sealed portion can be suppressed, and it is easy to obtain excellent heat sealability and excellent cold impact resistance.
[0037] The ethylene-propylene copolymer elastomer (D) may have a melt flow rate (MFR: ISO 1133) (temperature 230°C, load 2.16 kg) in the range of 0.5 to 3.5 g / 10 min. When the melt flow rate is equal to or higher than the lower limit, the load on the extruder during molding is small, the processing speed is unlikely to decrease, and it is easy to maintain excellent productivity. When the melt flow rate is equal to or lower than the upper limit, the compatibility between the propylene-ethylene block copolymer (C) and the ethylene-propylene copolymer elastomer (D) is good, and transparency is unlikely to decrease.
[0038] The ethylene-propylene copolymer elastomer (D) may have a ratio of propylene content to ethylene content (propylene content / ethylene content) in the range of 1.5 to 4. When the ratio is equal to or greater than the lower limit, the flexibility of the film is maintained, edge tearing of the heat-sealed portion after retort treatment can be suppressed, and excellent heat sealability can be easily obtained. When the ratio is equal to or less than the upper limit, the compatibility between the propylene-ethylene block copolymer (C) and the ethylene-propylene copolymer elastomer (D) is good, and transparency is less likely to decrease.
[0039] The inner layer may contain 90 to 50 parts by mass of the propylene-ethylene block copolymer (C) and 10 to 50 parts by mass of the ethylene-propylene copolymer elastomer (D). When the content of the propylene-ethylene block copolymer (C) is 50 parts by mass or more, excellent heat sealability is easily maintained. When the content of the propylene-ethylene block copolymer (C) is 90 parts by mass or less, that is, when the content of the ethylene-propylene copolymer elastomer (D) is at least 10 parts by mass or more, further excellent heat sealability and excellent cold impact resistance can be exhibited. From these viewpoints, the inner layer may contain 80 to 60 parts by mass of the propylene-ethylene block copolymer (C) and 20 to 40 parts by mass of the ethylene-propylene copolymer elastomer (D).
[0040] [Zinc oxide particles] At least one of the inner layer and the second outer layer further contains zinc oxide particles. The content of the zinc oxide particles per unit area of the multilayer film is 0.030 to 0.25 g / m 2 The thickness can be set to 0.045 to 0.18 g / m 2 and may be 0.09 to 0.15 g / m 2It may be. When the content of zinc oxide particles is equal to or more than the lower limit, excellent odor adsorption can be obtained, and when it is equal to or less than the upper limit, excellent transparency can be exhibited. The unit area of the multilayer film can be said to be the unit area of the inner layer when zinc oxide particles are contained only in the inner layer, and the unit area of the second outer layer when zinc oxide particles are contained only in the second outer layer. The content of zinc oxide particles in each layer can be adjusted by changing the amount of zinc oxide particles added or the thickness of the layer.
[0041] The average spherical equivalent diameter of the zinc oxide particles can be 100 nm or less, and may be 90 nm or less. This increases the surface area of the zinc oxide particles, and allows them to exhibit excellent odor adsorption properties, and also allows them to exhibit excellent transparency by suppressing light dispersion. The lower limit of the average spherical equivalent diameter is not particularly limited, but can be 20 nm or more from the viewpoint of suppressing re-aggregation of the zinc oxide particles.
[0042] [How to calculate the sphere-equivalent diameter of zinc oxide] After embedding the multilayer film containing zinc oxide particles in epoxy resin, trimming, surface preparation, and preparation of ultrathin sections are performed using an ultramicrotome equipped with a diamond knife. The cross section of the ultrathin section (layer containing zinc oxide particles) is then observed at a magnification of 50,000 times using a scanning transmission electron microscope. A three-dimensional reconstruction image of the observed image is created using the 3D reconstruction software "Composer". Then, using image analysis software (FEI, model number Avizo2019.2), the volume of each zinc oxide particle observed in the range of 3281 nm x 3281 nm x 625 nm is calculated, and the diameter of a sphere equivalent to that volume is calculated, and the average value is taken as the average spherical equivalent diameter.
[0043] The thickness of the multilayer film is not particularly limited as long as it can be used as a film for packaging materials, but if the film is too thick, it will be cost-intensive. Therefore, the thickness of the multilayer film can be 100 μm or less, and may be 50 to 70 μm.
[0044] The thickness of the outer layer (i.e., the total thickness of the first outer layer and the second outer layer) may be 25 to 42% based on the thickness of the multilayer film. When the ratio of the thickness of the outer layer is equal to or more than the lower limit, excellent transparency is easily obtained, and when it is equal to or less than the upper limit, deterioration of the heat sealability of the film can be suppressed, making it easy to obtain practical use.
[0045] The thickness of the outer layer (i.e., the total thickness of the first outer layer and the second outer layer) may be 10 μm or more, or 15 μm or more. This makes it easy to ensure the transparency of the film and makes it difficult for the heat seal strength to decrease. The upper limit of the thickness of the outer layer is not particularly limited, but it can be 40 μm or less, or may be 30 μm or less, or may be 20 μm or less, so that cold impact resistance is easily ensured.
[0046] The thickness of the inner layer may be 30 μm or more, or 35 μm or more. This maintains the flexibility of the film, makes the film less likely to break after retort treatment, and makes the heat seal strength less likely to decrease. The upper limit of the thickness of the inner layer is not particularly limited, but may be 80 μm or less, 70 μm or less, or 50 μm or less, for example, from the viewpoint of cost.
[0047] <Manufacturing method of multilayer film> The method for producing the multilayer film is not particularly limited, and known methods can be used. For example, examples of the thermoforming process include a melt-kneading method using a general mixer such as a single-screw extruder, a twin-screw extruder, or a multi-screw extruder, and a method in which the components are dissolved or dispersed and mixed, and then the solvent is removed by heating. In consideration of workability, a single-screw extruder or a twin-screw extruder can be used. When a single-screw extruder is used, the screw can be a full-flight screw, a screw with a mixing element, a barrier flight screw, a fluted screw, or the like, which can be used without any particular restrictions. As the twin-screw kneading device, a co-rotating twin-screw extruder, a counter-rotating twin-screw extruder, or the like can be used, and the screw shape can be a full-flight screw, a kneading disk type, or the like, which can be used without any particular restrictions.
[0048] In the above method, it is possible to use a method in which the multilayer film is melted using a single screw extruder or twin screw extruder, etc., and then formed into a film using a T-die via a feed block or a multi-manifold.
[0049] The obtained multilayer film may be subjected to a surface modification treatment to improve suitability for subsequent processes as necessary. For example, in order to improve printability when used as a single film or lamination suitability when used in a laminated form, a surface modification treatment may be performed on the printing surface or the surface that comes into contact with the substrate. Examples of the surface modification treatment include treatments such as corona discharge treatment, plasma treatment, and frame treatment that oxidize the film surface to generate functional groups, and modification treatments by a wet process that forms an easy-adhesion layer by coating.
[0050] <Packaging material> The multilayer film may be used as a single film or may be laminated with a substrate, and the method of use as a packaging material is not particularly limited.
[0051] When the multilayer film is laminated with a substrate, the packaging material can include the multilayer film and the substrate. Specifically, such a packaging material can be obtained by laminating at least one layer of a substrate such as a biaxially oriented polyamide film (ONy), a biaxially oriented polyester film (PET), a printed paper, a metal foil (AL foil), or a transparent vapor deposition film onto the multilayer film 10 to form a laminate. FIG. 2 is a cross-sectional view of a packaging material according to one embodiment of the present invention. The packaging material 100 shown in the figure includes a multilayer film 10, an adhesive layer 3, a substrate film 4, an adhesive layer 5, and a transparent vapor deposition film 6 in this order. The laminate can be produced by a normal dry lamination method in which the films constituting the laminate are bonded together using an adhesive, but if necessary, a method in which the multilayer film is directly extrusion laminated onto the substrate can also be used.
[0052] The laminate structure of the laminate can be adjusted appropriately according to the required properties of the packaging material, such as barrier properties that meet the shelf life of the packaged food, size and impact resistance to accommodate the weight of the contents, visibility of the contents, etc.
[0053] <Package> The packaging body may be made from the above packaging material, and there is no particular restriction on the form of the bag. For example, the above packaging material (laminate) can be used for a flat bag, a three-sided bag, a palm-shaped bag, a gusseted bag, a standing pouch, a pouch with a spout, a pouch with a beak, etc., using a multilayer film as a sealing material. EXAMPLES
[0054] The present invention will be described in detail below using examples, but the present invention is not limited to the following examples.
[0055] <Preparation of various materials> The following propylene homopolymer (A), propylene-ethylene random copolymer (B), propylene-ethylene block copolymer (C), ethylene-propylene copolymer elastomer (D), zinc oxide masterbatches (E) and (F) were prepared.
[0056] (Propylene homopolymer (A)) A propylene homopolymer having a melting onset temperature of 153°C, a melting peak temperature of 159°C, and a melt flow rate (MFR: ISO 1133) (temperature 230°C, load 2.16 kg) of 3.0 g / 10 min when measured by differential scanning calorimetry (JIS K 7121).
[0057] (Propylene-ethylene random copolymer (B)) When measured by differential scanning calorimetry (JIS K 7121), the melting start temperature was 142°C, the melting peak temperature was 147°C, and ΔH h / ΔH l A propylene-ethylene random copolymer having a molecular weight of 1.84 and an ethylene content of 3.4 mass%.
[0058] The ethylene content was measured according to the ethylene content determination method (IR method) described on pages 412-413 of the Polymer Analysis Handbook (May 10, 2013, 3rd printing) edited by the Polymer Analysis Roundtable of the Japan Analytical Society. ΔH h / ΔH l is the heat of fusion ΔH on the higher side of the measurement temperature 135°C when differential scanning calorimetry (JIS K 7121) is performed. h and the heat of fusion on the low temperature side ΔH l Figure 3 shows the total heat of fusion of the propylene-ethylene random copolymer (B) and the result of dividing the heat of fusion at 135°C.
[0059] (Propylene-ethylene block copolymer (C)) A propylene-ethylene block copolymer having a melt flow rate (MFR: ISO 1133) (temperature 230°C, load 2.16 kg) of 2.0 g / 10 min., containing 77.1 mass % propylene polymer and 22.9 mass % ethylene-propylene copolymer, with the ethylene content of the ethylene-propylene copolymer being 28.7 mass %.
[0060] (Ethylene-propylene copolymer elastomer (D)) An ethylene-propylene copolymer elastomer with a melt flow rate (MFR: ISO 1133) (temperature 230°C, load 2.16 kg) of 0.6 g / 10 min and a propylene content / ethylene content of 2.7.
[0061] (Zinc oxide masterbatch (E)) A zinc oxide masterbatch prepared by melt-mixing 20% by mass of zinc oxide particles having a primary particle size of 35 nm and having the particle surface coated with a high-density silica layer and a polysiloxane layer in that order, with 80% by mass of polypropylene resin.
[0062] (Zinc oxide masterbatch (F)) A zinc oxide masterbatch prepared by melt-mixing 20% by mass of zinc oxide particles with a primary particle size of 35 nm and no coating treatment on the particle surface with 80% by mass of polypropylene resin.
[0063] <Preparation of laminated film> Example 1 For the outer layer, a resin mixture was used in which 50 parts by mass of propylene homopolymer (A) and 50 parts by mass of propylene-ethylene random copolymer (B) were mixed in the form of pellets. For the inner layer, 67.8 parts by mass of propylene-ethylene block copolymer (C) and 32.2 parts by mass of ethylene-propylene copolymer elastomer (D) were mixed in the form of pellets, and 0.63 parts by mass of zinc oxide master batch (E) was further mixed with 100 parts by mass of propylene-ethylene block copolymer (C) and ethylene-propylene copolymer elastomer (D). After the layer formation, the zinc oxide content in the inner layer was 0.045 g / m 2 The respective raw materials were fed to an extruder whose temperature was adjusted to 250° C., kneaded in a molten state, and laminated in a T-die extruder having a feed block so that the first outer layer and the second outer layer had a thickness of 10 μm, and the inner layer had a thickness of 40 μm, thereby producing the film of Example 1.
[0064] Example 2 A film of Example 2 was produced in the same manner as in Example 1, except that the blending ratio of the zinc oxide master batch (E) was changed as shown in Table 1.
[0065] Example 3 A film of Example 3 was produced in the same manner as in Example 2, except that the zinc oxide masterbatch (E) was changed to the zinc oxide masterbatch (F).
[0066] Example 4 A film of Example 4 was produced in the same manner as in Example 3, except that the blending ratio of the zinc oxide master batch (F) was changed as shown in Table 1.
[0067] Example 5 A film of Example 5 was produced in the same manner as in Example 1, except that the blending ratio of the zinc oxide master batch (E) was changed as shown in Table 1.
[0068] Example 6 The film of Example 6 was produced in the same manner as in Example 1, except that the layer containing the zinc oxide masterbatch (E) was changed to the second outer layer, and a resin mixture in which 5.21 parts by mass of the zinc oxide masterbatch (E) was mixed with 100 parts by mass of the propylene homopolymer (A) and the propylene-ethylene random copolymer (B) was used.
[0069] Example 7 The film of Example 7 was produced in the same manner as in Example 6, except that the blending ratio of the zinc oxide master batch (E) was changed as shown in Table 1.
[0070] Comparative Example 1 A film of Comparative Example 1 was produced in the same manner as in Example 1, except that the blending ratio of the zinc oxide master batch (E) was changed as shown in Table 1.
[0071] Comparative Example 2 A film of Comparative Example 2 was produced in the same manner as in Example 3, except that the blending ratio of the zinc oxide master batch (F) was changed as shown in Table 1.
[0072] Comparative Example 3 A film of Comparative Example 3 was produced in the same manner as in Example 6, except that the blending ratio of the zinc oxide master batch (E) was changed as shown in Table 1.
[0073] Comparative Example 4 A film of Comparative Example 4 was produced in the same manner as in Example 3, except that the blending ratio of the zinc oxide master batch (F) was changed as shown in Table 1.
[0074] Comparative Example 5 A film of Comparative Example 5 was produced in the same manner as in Example 1, except that the blending ratio of the zinc oxide master batch (E) was changed as shown in Table 1.
[0075] <Various evaluations> The films obtained in each example were subjected to the following evaluations, and the results are shown in Table 1.
[0076] [Zinc oxide mean spherical equivalent diameter] The film obtained in each example was embedded in epoxy resin, and then trimmed, surfaced, and ultrathin sections were prepared using an ultramicrotome equipped with a diamond knife. Then, a scanning transmission electron microscope was used to observe the cross section of the ultrathin section (a layer containing zinc oxide particles) at a magnification of 50,000 times, and a three-dimensional reconstruction image of the observed image was created using the 3D reconstruction software "Composer". Then, using image analysis software (FEI, model number Avizo2019.2), the volume of each zinc oxide particle observed in the range of 3281 nm x 3281 nm x 625 nm was calculated, the diameter of a sphere equivalent to that volume was calculated, and the average value was taken as the average equivalent sphere diameter. Figure 4 is a distribution diagram of the equivalent sphere diameter of zinc oxide particles in the film prepared in Example 1.
[0077] [Haze measurement after retort] The first outer layers of the films (polypropylene multilayer films) obtained in each example were placed facing each other and heat sealed using a heat sealer manufactured by Tester Sangyo Co., Ltd. under the conditions of a sealing pressure of 0.2 MPa, a sealing time of 1 second, a sealing width of 5 mm, and a sealing temperature of 200°C. Then, the films were filled with water and retorted at 135°C for 40 minutes. The retorted films were evaluated using a haze meter (model number HM-150) manufactured by Murakami Color Research Laboratory in accordance with the haze measurement method described in JISK7136.
[0078] [Hydrogen sulfide reduction rate] A 12 μm thick biaxially oriented polyester film (PET), a 15 μm thick biaxially oriented polyamide film (ONy), a 7 μm thick AL foil, and the film obtained in each example (polypropylene film) were bonded together using a urethane adhesive by a conventional dry lamination method to form a laminate with the following configuration. Laminate structure: PET / adhesive / ONy / adhesive / AL foil / adhesive / polypropylene film The polypropylene films of this laminate were placed facing each other, and heat-sealed using a heat sealer manufactured by Tester Sangyo Co., Ltd. under the conditions of a sealing pressure of 0.2 MPa, a sealing time of 1 second, a sealing width of 5 mm, and a sealing temperature of 200°C to produce a packaging bag (three-sided bag). Then, an aqueous cysteine solution containing 0.03% by mass of L-cysteine was filled into the packaging bag, and retorted at 135°C for 40 minutes. After the retort treatment, the solution in the packaging bag was collected, and the hydrogen sulfide reduction rate was measured using a Pack Test (model number WAK-S) manufactured by Kyoritsu Rikagaku Kenkyusho Co., Ltd. The hydrogen sulfide reduction rate was calculated by reacting the collected solution with a Pack Test reagent, measuring the absorbance at a wavelength of 668 nm with a spectrophotometer, and calculating the reduction rate of the absorbance evaluated using the film obtained in each example relative to the absorbance measured using a packaging bag not containing zinc oxide.
[0079] [Heat sealability evaluation] Packaging bags (three-sided bags) were prepared in the same manner as above, then filled with water and retorted for 40 minutes at 135° C. The retorted film was cut into a 15 mm wide x 80 mm piece and subjected to T-peel at a tensile speed of 300 mm / min using a tensile tester manufactured by Shimadzu Corporation to measure the heat seal strength.
[0080] [Cold impact resistance evaluation] Using a film impact tester manufactured by Toyo Seiki Co., Ltd., the cold impact resistance of the films obtained in each example was evaluated under conditions of a temperature of -5°C, a weight of 1.5 J, and a bullet size of 1.5 inches.
[0081] [Table 1] [Industrial Applicability]
[0082] The polypropylene-based multilayer film of the present invention has excellent odor adsorption properties against the sulfur odor generated from retort foods, and also has high transparency necessary for visually checking the contents, and can be suitably used as a sealant film for retort packaging. [Explanation of symbols]
[0083] 10...multilayer film, 100...packaging material, 1a...first outer layer, 1b...second outer layer, 2...inner layer, 3...adhesive layer, 4...base film, 5...adhesive layer, 6...transparent vapor deposition film.
Claims
1. a first outer layer which is a heat seal layer containing a propylene homopolymer (A) and a propylene-ethylene random copolymer (B); an inner layer containing a propylene-ethylene block copolymer (C) and an ethylene-propylene copolymer elastomer (D); a second outer layer containing a propylene homopolymer (A) and a propylene-ethylene random copolymer (B) in this order; At least one of the inner layer and the second outer layer further contains zinc oxide particles, and the content of the zinc oxide particles per unit area of the multilayer film is 0.030 to 0.25 g / m 2 A multi-layer film.
2. 2. The multilayer film according to claim 1, wherein the zinc oxide particles have an average equivalent sphere diameter of 100 nm or less.
3. 3. The multilayer film according to claim 1, wherein the first outer layer and the second outer layer each contain 70 to 30 parts by mass of the propylene homopolymer (A) and 30 to 70 parts by mass of the propylene-ethylene random copolymer (B) having an ethylene content of 5 mass% or less, and the second outer layer further contains the zinc oxide particles.
4. 3. The multilayer film according to claim 1, wherein the inner layer contains 90 to 50 parts by mass of the propylene-ethylene block copolymer (C) and 10 to 50 parts by mass of the ethylene-propylene copolymer elastomer (D), and the inner layer further contains the zinc oxide particles.
5. The multilayer film according to any one of claims 1 to 4, wherein the total thickness of the first outer layer and the second outer layer is 25 to 42% based on the thickness of the multilayer film.
6. The multilayer film according to any one of claims 1 to 5, wherein the inner layer has a thickness of 30 µm or more.
7. A packaging material comprising the multilayer film according to any one of claims 1 to 6 and a substrate.
8. A package produced from the packaging material according to claim 7.
Citation Information
Patent Citations
Polyolefin film for retort
JP1997248885A
Resin laminate and its application
JP1997262948A
Propylene resin multilayer sheet, and package for heating treatment using the same
JP2012006250A
Polypropylene vertically uniaxially stretched film and film laminate, and bag-like object
JP2019018435A
Laminate and package
JP2019195953A